Motivating your secondary class - Galton, Maurice J.
Galton and his team have collected examples from across the country of what works in re-energizing demotivated pupils. This book presents practical advice and strategies for improving lower secondary school classrooms, ranging from reducing class size to innovative induction programmes
Keywords: Motivation in education -- Great Britain; Effective teaching -- Great Britain; High school teaching -- Great Britain; Motivation; High school; Unterricht; Großbritannien; Aufsatzsammlung